'Just Enough' Piracy Can Be a Good Thing - Kim, Antino (MIT Sloan Management Review, 2019)
When piracy is rampant, its negative impact makes manufacturers and retailers worse off - but anti-piracy measures are often expensive. Before going full force against piracy, organizations should ponder whether doing so would be a worthwhile investment. One factor to consider: Research shows that a moderate level of piracy - not too much, not too little - can actually benefit the manufacturer, the retailer, and consumers, all at the same time.
Online resource; Title from title page (viewed August 27, 2019)
Keywords: Electronic books; local